Nephrogenic Syndrome of Inappropriate Antidiuresis - D. Morin; J. Tenenbaum; B. Ranchin; T. Durroux (Hindawi Limited, 2012)
Mutations in the vasopressin V2 receptor gene are responsible for two human tubular disorders: X-linked congenital nephrogenic diabetes insipidus, due to a loss of function of the mutant V2 receptor, and the nephrogenic syndrome of inappropriate antidiuresis, due to a constitutive activation of the mutant V2 receptor. This latter recently described disease may be diagnosed from infancy to adulthood, as some carriers remain asymptomatic for many years. Symptomatic children, however, typically present with clinical and biological features suggesting inappropriate antidiuretic hormone secretion with severe hyponatremia and high urine osmolality, but a low plasma arginine vasopressin level. To date, only two missense mutations in the vasopressin V2 receptor gene have been found in the reported patients. The pathophysiology of the disease requires fuller elucidation as the phenotypic variability observed in patients bearing the same mutations remains unexplained. The treatment is mainly preventive with fluid restriction, but urea may also be proposed.